Crime prevention through environmental design (CPTED) in Western Australia: planning for sustainable urban futures - Cozens, Paul (WIT Press, 2008)
Purpose: Cities as places of human habitation have multiple and interwoven impacts on the environment and upon their inhabitants. There are many definitions and interpretations of sustainable development and various models exist for the sustainable city, ranging from 'light green' to 'dark green'. This paper discusses the 'redesigning the city' model [1] and investigates the extent to which crime and fear of crime are integrated within this framework and argues Crime Prevention Through Environmental Design (CPTED) represents a useful planning tool to assist in the development of urban sustainability.Results: A review of the literature clearly indicates that crime and fear of crime need to be considered within sustainability frameworks and that these issues can seriously undermine the broader aims of urban sustainability. If sustainability is to adequately represent the new large-scale vision to guide the planning agenda for the twenty-first century [2] it must incorporate a primary consideration for all potential threats to the long-term sustainable health and personal safety of both the built environment and of its occupants.Conclusions: The paper concludes that such issues as crime and the fear of crime are not effectively represented within most sustainability agendas, and require explicit inclusion. Analysts tend to focus on levels of recorded crime, largely ignoring the crucial and arguably more important dimension, of citizens' fear of crime and their perceptions of the built environment. This paper provides recommendations for integrating crime and fear of crime within urban sustainability. It also proposes that 'designing out crime', also known as CPTED, represents a vital tool for assisting in the creation, development and promotion of more user friendly and sustainable urban environments.